Civilians and modern war : armed conflict and the ideology of violence - Rothbart, Daniel; Korostelina, K. V. (Karina Valentinovna).; Cherkaoui, Mohammed D., 1960- (London : Routledge, 2012)
This text explores the issue of civilian devastation in modern warfare, focusing on the complex processes that effectively establish civilians' identity in times of war.
The place and plight of civilians in modern war / Daniel Rothbart, Karina Korostelina, and Mohammed D. Cherkaoui -- Targeting civilians -- The role of civilians in American war ideology / Richard Rubenstein -- Devastating civilians at home: the plight of Crimean Tatars and Californians of Asian descent during World War II / Karina Korostelina -- Military culture and civilian victimization: the case of American strategic bombing in World War II / Alexander Downes -- Double victims: the recruitment and treatment of child soldiers in Chechnya / Karina Korostelina & Juliia Kononenko -- Preserving civilian immunity -- The politics of civilian identity / Daniel Rothbart -- Israeli soldiers' perceptions of Palestinian civilians during the 2009 Gaza War / Neta Oren -- Civilian vulnerability in asymmetric conflict: lessons from the second Lebanon and Gaza Wars / Michael Gross -- Civilians overshadowed by soldiers: faceless victims of the public media narrative / Mohammed D. Cherkaoui -- Civilians, pundits, and the mediatized ideology / Mohammed D. Cherkaoui -- Redressing anti-civilian practices -- Trans-regional military dimensions of civilian protection: a two-part problem with a two-part solution / Donald C. F. Daniel and Tromila Wheat -- Civilians under the law: inequality, intersectionality, and irony / Susan Hirsch -- The price of justice / Michael Miklaucic -- Preventing genocide: the quest for system response / Andrea Bartoli and Testushi Ogata -- Making amends / Sarah Holewinski -- Conclusion: the road ahead / Daniel Rothbart, Karina Korostelina, and Mohammed D. Cherkaoui.
Keywords: Civilians in war; Combatants and noncombatants (International law).; Military history, Modern -- 20th century; Military history, Modern -- 21st century